2022
DOI: 10.3390/ijerph192316154
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depression, Anxiety, and Stress among High School Students during the COVID-19 Pandemic: A Survey Study in Western Mexico

Abstract: Social isolation and school closure may predispose adolescents to higher prevalence rates of depression, anxiety, and stress. In this cross-sectional observational study, the validated Spanish version of the Depression, Anxiety, and Stress Scale was administered to 3112 students aged 14–22 years old. We also collected data on participant gender, age group, school shift (morning or afternoon), school year, family type, whether they or any first-degree relative had been infected with COVID-19, whether any family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Consequently, further subgroup analyses should be utilized. The literature have shown that the rates of depression and anxiety rose during the COVID-19 pandemic, which corresponds to the period during which our sample was collected, suggesting that this age group is more susceptible to depression and stress symptoms during this time [37][38][39].…”
Section: Discussionmentioning
confidence: 88%
“…Consequently, further subgroup analyses should be utilized. The literature have shown that the rates of depression and anxiety rose during the COVID-19 pandemic, which corresponds to the period during which our sample was collected, suggesting that this age group is more susceptible to depression and stress symptoms during this time [37][38][39].…”
Section: Discussionmentioning
confidence: 88%
“…Bad teachers will increase student anxiety when learning (Stomff, 2014). Online learning systems, such as during the COVID-19 pandemic, also caused students to feel anxious, stressed, and depressed (Cervantes-Cardona et al, 2022). In addition, practical learning in the laboratory also increases student anxiety (Kurbanoglu & Akim, 2010).…”
Section: Problem Statementmentioning
confidence: 99%
“…Compared with adults, they were also more likely to suffer from PTSD and emotional problems ( 9 , 10 ). During the COVID-19 pandemic, it was found that adolescents infected with COVID-19 exhibited a higher incidence of depression and anxiety ( 11 ), and adolescents infected with COVID-19 exhibited a higher risk of mental disorders, including anxiety, depression, post traumatic stress disorder, and sleep disorders ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that: In a study of 8,079 adolescents in China, the prevalence of depression was as high as 43%, anxiety was as high as 37%, and combined symptoms of depression and anxiety were as high as 31%. Compared with adults, they were also more likely to suffer from PTSD and emotional problems (9,10). During the COVID-19 pandemic, it was found that adolescents infected with COVID-19 exhibited a higher incidence of depression and anxiety (11), and adolescents infected with COVID-19 exhibited a higher risk of mental disorders, including anxiety, depression, post traumatic stress disorder, and sleep disorders (12).…”
Section: Introductionmentioning
confidence: 99%